Increasing Incidence of Malignancy Among Male Breast Lesions in The Urban Population of India - Mallick, Sujata; Mallik, Mahasweta (Annals of Pathology and Laboratory Medicine, 2018)
Background: Among the male breast lesion gynaecomastia is the most common lesion present. Breast malignancy accounts for less than 1% of all male malignancy. Aim of this study was to see the increasing incidence of breast carcinoma among males in India Methods: A retrospective study was undertaken in KPC Medical College, catering to an urban population, over a period of three and a half years. 32 male breast lesions which presented in the surgery department were analysed. Result: 75% of the cases were gynaecomastia which is the most common male breast lesion,other benign breast lesions like epidermal cyst, breast abscess and fibroadenoma comprised 9.3% of the total lesions present. Breast carcinoma, In situ lesion and sarcoma of the breast accounted for 15.5% of the cases. Conclusion: Worldwide studies have shown male breast carcinoma to be less than 1%. Our study showed a prevalence of 15.5% breast malignancy, showing a phenomenal increase in breast carcinoma among male patient.